2022
DOI: 10.48550/arxiv.2201.02636
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A survey of high-$z$ galaxies: SERRA simulations

A. Pallottini,
A. Ferrara,
S. Gallerani
et al.

Abstract: We introduce serra, a suite of zoom-in high-resolution (∼ 10 pc) cosmological simulations including non-equilibrium chemistry and on-the-fly radiative transfer. The outputs are post-processed to derive galaxy UV+FIR continuum and emission line properties. Results are compared with available multi-wavelength data to constrain the physical properties (e.g., star formation rates, stellar/gas/dust mass, metallicity) of high-redshift 6 < ∼ z < ∼ 15 galaxies. This flagship paper focuses on the z = 7.7 sub-sample, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 205 publications
(178 reference statements)
5
9
0
1
Order By: Relevance
“…We also tested our method on simulations, applying it to the z ∼ 6.7 galaxy Zinnia (a.k.a. serra05:s46:h0643) from the SERRA simulation suite (Pallottini et al 2019, see also Pallottini et al 2022). Also in this case, we recover T d in agreement with single-temperature grey body SED fitting performed at the frequencies corresponding to ALMA bands 6, 7, and 8.…”
Section: Methodssupporting
confidence: 80%
See 2 more Smart Citations
“…We also tested our method on simulations, applying it to the z ∼ 6.7 galaxy Zinnia (a.k.a. serra05:s46:h0643) from the SERRA simulation suite (Pallottini et al 2019, see also Pallottini et al 2022). Also in this case, we recover T d in agreement with single-temperature grey body SED fitting performed at the frequencies corresponding to ALMA bands 6, 7, and 8.…”
Section: Methodssupporting
confidence: 80%
“…Finally the lower dust-tometal ratio predicted for early galaxies from simulations at z > ∼ 5 (see e.g. Aoyama et al 2017;Behrens et al 2018;Shen et al 2021;Pallottini et al 2022) could also motivate the presence of hot dust at high-z. In fact, a lower dust content results in warmer dust temperatures for a given L FIR .…”
Section: Dust Temperature Evolutionmentioning
confidence: 95%
See 1 more Smart Citation
“…As pointed by Ferrara et al (2019), massive high-redshift galaxies correspond much high [CII] surface brightness regime than the initial low-redshift De Looze et al ( 2014) observations and it is almost surprising that this relation remains valid under these physical conditions. While numerical simulations (Arata et al 2020;Pallottini et al 2019Pallottini et al , 2022 predict that the local relation is respected also for M < 10 9 M galaxies, we currently have no strong observational support for this and we cannot guarantee that a [CII]-deficit does not appear at low-mass (M < 10 9.5 M ) or higher redshift (z>6), where the metallicity is expected to be much lower. To test this scenario, we also implemented the Lagache et al (2018, hereafter L18) relation predicted by a semi-analytical model, which produce a lower [CII] luminosity at higher redshifts and lower SFRs:…”
Section: [Cii] Emissionmentioning
confidence: 75%
“…Observational studies at low redshift (e.g., De Looze et al 2014;Herrera-Camus et al 2015) and high redshift (e.g., Capak et al 2015;Schaerer et al 2020;Carniani et al 2020) found a non-evolving and nearlylinear empirical correlation between [CII] luminosity and SFR. Both numerical simulations (Vallini et al 2015;Olsen et al 2017;Lupi & Bovino 2020;Pallottini et al 2022) and semianalytical models (Lagache et al 2018;Popping et al 2019) predict a weakly evolving relation with redshift. The [CII] line is thus a suitable tracer of the high-z star formation at large scales.…”
Section: Introductionmentioning
confidence: 96%